PRODUCT QUALITY, PRODUCT DESIGN, AND BRAND IMAGE INFLUENCE ON THE DECISION TO PURCHASE A REALME SMARTPHONE IN PADANG CITY - Fatmawati, Jihan; Wati, Linda (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
This study aims to empirically examine the influence of product quality, product design, and brand image on realme smartphone purchase decisions. This study is quantitative and uses primary data obtained through questionnaires. The population of this study is the entire consumer of realme smartphone users in Padang City. Sampling technique is purposive sampling. A sample of 150 respondents was obtained. Data analysis with the help of SPSS software version 26. The results of this study showed that the quality of the product has a partial influence on the purchase decision, the design of the producer has a partial influence on the decision of the purchaser, and the The image of the brand has no influence in part on the purchasing decision.